ANALISIS GAYA DIAFRAGMA, KORD, DAN KOLEKTOR PADA STRUKTUR GEDUNG OVAL RSUD AR ROZY KOTA PROBOLINGGO - Adam Rachmat Edijana; Made Dharma Astawa; Wahyu Kartini (LPPM Universitas Abdurrab, 2025)
The oval building structure of Ar-Rozy Regional Hospital in Probolinggo has non-parallel system horizontal irregularities due to the configuration of lateral restraint elements in the structure not parallel to its orthogonal axis. Structural failure due to irregularities can be anticipated by planning diaphragm elements. In this article, the design and calculation of diaphragm force, chord, and collector to ensure the safety of the structure in resisting lateral forces. The results in this article show that the diaphragm force design for stories 1-14 uses the minimum force (Fpx min), while for stories 15-16, it uses the diaphragm design force (Fpx). The chord element in the weak axis direction requires 6D22 reinforcement, while in the strong axis direction, it requires 3D22 reinforcement. The collector element in beam B1-A that has been designed requires additional 2D22 reinforcement and is installed in the center of the beam cross-section because beam B1-A as a collector element must have the ability to withstand axial-flexural forces due to the combination of collector design forces.